Beyond transgression: mountain biking, young people and managing green spaces. Issue 2 (14th March 2020) - King, Katherine; Church, Andrew
ABSTRACT: The importance of regular participation in physical activity in youth has seen attention turn to the role of lifestyle sports. Existing research on lifestyle sports lacks consideration of young people's use of green spaces and the approaches of managers to conflicts in these spaces. Young people's experiences of leisure are closely tied to those who oversee their use of leisure spaces and this paper is a rare example of research that draws upon qualitative methods from 40 mountain biking participants and 9 managers to explore both perspectives. Findings reveal young people seek opportunities for autonomy in green spaces through mountain biking but contest normative management practices. Managers recognized the benefits of engaging young people in mountain biking and discussed experimenting with various strategies to accommodate their practices. The paper therefore discusses the importance of moving beyond constructions of young people's participation in lifestyle sports as transgressive and troublesome.